Teachers’ Perspectives on Bullying: A Crucial Step Towards Safer School Environments - Wardhani, Dhian Putri; Wijayanto, Agus; Laila, Malikatul (FKIP Universitas Lampung, 2024)
Abstract: Teachers’ Perspectives on Bullying: A Crucial Step Towards Safer School Environments. Objectives: This study aims to examine teachers’ understanding of bullying acts. Method: This study is qualitative research with a case study approach. A semi-structured interview and Multimedia Discourse Completion Tasks (MDCTs) were employed to collect the research data. Findings: The findings revealed that almost all the teacher participants possess an excellent understanding of bullying. They based their examination of bullying acts on several risk factors, such as physical features or body build, externalizing behaviour, self-esteem, social skills and popularity, and delinquency. Additionally, the foundations they utilized in categorizing bullying acts included intent to hurt, power disparity, and long-term repetition. Conclusion: In conclusion, teachers are expected to be more sensitive to bullying acts and they can use their knowledge to prevent bullying in the school environment. Keywords: bullying, teacher’s understanding of bullying, bullying risk factors, bullying categories.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202421